LANGUAGE PHILOSOPHY - M. N. Nuritdinov (Modern American Journals, 2025)
Let us consider another unique aspect of philosophical thought in Islam. Long before the beginning of the Islamic era, the Syrians and Iranians studied Aristotle's hermeneutics, as revised by the Stoics and Neoplatonists. Thanks to the friendship between the famous Zoroastrian Ibn Muqaffa (who later converted to Islam) and the philologist Khalil (d. 791), Muslim scholars had the opportunity to study works on logic and grammar written in Middle Persian (Pahlavi).